Active control experiments on a Levy cable dome. (1st March 2023) - Zhang, Haiying; Lu, Jinyu; Lu, Meng; Li, Na
Highlights: Force optimization control effect of the structure is investigated through experimental research. A new type actuation control system for the active members is designed. After actuation, the internal force of all the components reduced significantly. Abstract: The traditional structure can only rely on the original design scheme to passively resist the changes in the external environment. Once the structure is damaged, it will bring heavy losses to the society. This paper introduces a Levy form cable dome, which can change its shape and internal force by changing the length of the active members to improve its adaptability to current loading conditions. The structure was composed of 2 hoop cables, 17 compressed struts, the central strut was designed to function as an actuator, and the internal force optimization control effect of the structure was investigated through experiments and numerical simulations. Firstly, the internal force optimization control model of the structure was established, and the optimal actuation amount of the actuator was obtained through the intelligent algorithm solutions. Then a detailed internal force active control experiment was carried out on the cable dome, including the actuator actuation and actuation recovery process. Results showed that, after actuation, the internal force of each component reduced significantly, among which, the internal force of the outer hoop cable had the smallest reduction, about 15.00%, and the internal force of each ridge cable had the largest reduction, around 50.00%. The internal force of each component increased with the actuation recovery of the actuator, and recovered to more than 90% of its initial prestress, indicating the accuracy of the designed actuation control system. The change trend of the experimental data is in good agreement with the simulation results, which verifies the correctness of the numerical calculation and the feasibility of the internal force optimization active control test of the structure under external loads by adjusting the length of its members.